Functional recovery in a rare case of an adult patient with leucodystrophy - Ganvir, Suvarna S.; Jethani, Simran M.; Gaikwad, Stuti N.; Harishchandre, Maheshwari (International Journal of Research in Medical Sciences, 2023)
The adulthood leukodystrophy is an uncommon clinical condition. Physiotherapy treatment provided to this referred patient resulted in a significant functional recovery within a short span of time inspite of gross lesion. A 34-year-old male patient diagnosed as a case of leucodystrophy was referred for Physiotherapy after 2 years of initial diagnosis physiotherapy progress consisted of increasing muscle strength, reducing tightness and improving postural stability; also to improve mobility for 5 months. After taking the pre and post assessment values of MAS, FIST, mFRT and FIM, improvement through the post assessment values showed significant functional recovery within 5 months. Significant functional recovery after 2 years of diagnosis of leucodystrophy provides promising scope of physiotherapy in future cases of leucodystrophy.